A New and Simple Risk Predictor of Contrast-Induced Nephropathy in Patients Undergoing Primary Percutaneous Coronary Intervention: TIMI Risk Index - Ahmet Kaya; Ahmet Karataş; Yasemin Kaya; Harun Düğeroğlu; Seçkin Dereli; Adil Bayramoğlu (Cardiology Research and Practice)
Background. The thrombolysis in myocardial infarction risk index (TRI) was developed to estimate prognosis at the initial contact of the healthcare provider in coronary artery disease patients without laboratory parameters. In this study, we aimed to investigate the relationship of the baseline TRI and contrast-induced nephropathy (CIN) in patients with ST-elevation myocardial infarction (STEMI). Methods. A total of 963 consecutive STEMI diagnosed patients who underwent primary percutaneous intervention were included in the study. TRI was calculated using the formula “heart rate × (age/10) 2/SBP” on admission. CIN was defined as an increase in serum creatinine concentration ≥25%, 48 hours later over the baseline. Results. Of the total of 963 patients, CIN was observed in 13% (n=128). TRI was significantly higher in the CIN (+) group compared with the CIN (−) group (32.9 ± 18.8 vs 19.9 ± 9.9, P<0.001). There was a stronger correlation between CIN and age, diastolic blood pressure, heart rate, Killip class, left ventricular ejection fraction, amount of contrast media, and diabetes mellitus. The amount of contrast media (OR 1.010, 95% CI 1.007–1.012, P<0.001) and TRI (OR 1.047, 95% CI 1.020–1.075, P=001) were independent predictors of CIN. The best threshold TRI for predicting CIN was ≥25.8, with a 67.1% sensitivity and 80.4% specificity (area under the curve (AUC): 0.740, 95% CI: 0.711–0.768, P<0.001). Conclusion. TRI is an independent predictor of CIN, and it may be used as a simple and reliable risk assessment of CIN in STEMI patients without the need for laboratory parameters.